PENINGKATAN KETERAMPILAN MEMBACA LANCAR MELALUI PERMAINAN SCRABBLEPADA SISWA KELAS I SEKOLAH DASAR (INCREASE READING CORECT THROUGH SCRABBLE GAMES THE STUDENTS OF FIRST CLASS ELEMENTARY SCHOOL) - Aminah, Aminah (Universitas Negeri Semarang, 2011)
Problem formulation in the research of this class action is 1) why scrabble games can increase teacher skill in IC class SDN Petompon 02 Semarang? 2) Why scrabble games can increase student activities in IC class SDN Petompon 02 Semarang? 3) Why scrabble games can increase reading correct? 4) why scrabble games can be contain of the text has purposes increase vocabulary. The Research subjects were class I students who amounted 40 children consisted of 22 boys and 18 girls. The research lasted during three cycles. Variables /factors were investigated in this research are the skills of teachers, student learning activies, reading corect, and contain of the text. Comparing the results between cycles I, cycle II with the cycle III and during the implementation of research result, then discussed with colleagues who acted as observers. Results of this research indicate an increase in the quality of teacher skills, student learning activities, reading corect,and contain of the textÃ‚Â through scrabble games. The average skill of teachers increased from 72,22% to the category of sufficient (cycle I) to 80,56% good category (cycle II) and 86,12% with a very good category (cycle III). The average student activities increased from 68,67% to the category sufficient (cycle I), became75,25% with a good category (cycle II), and became 82,67% with a very good category (cycle III). Reaiding corect increas from skor 13,25 good category (cycle I) increased from 13,63% very good kategory.Ã‚Â The contain the text creased from 72,5% (cycle I), became 77,5%(cycle II), and became 80% (cycle III). Based on results of this reading through scrabble games increased of teacher skill, increased ofÃ‚Â student learning activities, increased of reading corect, and increased contain of text. Key words: reading is corect, scrabble games